2017
DOI: 10.1002/2016jg003724
|View full text |Cite
|
Sign up to set email alerts
|

Coincident aboveground and belowground autonomous monitoring to quantify covariability in permafrost, soil, and vegetation properties in Arctic tundra

Abstract: Coincident monitoring of the spatiotemporal distribution of and interactions between land, soil, and permafrost properties is important for advancing our understanding of ecosystem dynamics. In this study, a novel monitoring strategy was developed to quantify complex Arctic ecosystem responses to the seasonal freeze‐thaw‐growing season conditions. The strategy exploited autonomous measurements obtained through electrical resistivity tomography to monitor soil properties, pole‐mounted optical cameras to monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 80 publications
4
68
0
Order By: Relevance
“…13) show that soil water thaws around the middle of June and freezes again around the middle of September. The thaw depth varies from 0.2 to 0.42 m. These results are compatible with our field survey data in Barrow (Dafflon et al, 2017), indicating that, although this is a synthetic study, its simulation is relatively compatible with the Arctic tundra field measurements. As for the influence of parameter uncertainties on the thaw depth estimation, we observed that the parameter uncertainties only cause thaw depth variations during the warmest period of the year (beginning of August to middle of September).…”
Section: Uncertainty Propagation From Parameters To the Hydrological-supporting
confidence: 80%
See 3 more Smart Citations
“…13) show that soil water thaws around the middle of June and freezes again around the middle of September. The thaw depth varies from 0.2 to 0.42 m. These results are compatible with our field survey data in Barrow (Dafflon et al, 2017), indicating that, although this is a synthetic study, its simulation is relatively compatible with the Arctic tundra field measurements. As for the influence of parameter uncertainties on the thaw depth estimation, we observed that the parameter uncertainties only cause thaw depth variations during the warmest period of the year (beginning of August to middle of September).…”
Section: Uncertainty Propagation From Parameters To the Hydrological-supporting
confidence: 80%
“…The bottom of the thaw layer at the end of the growing season is located at about 0.3 and 0.5 m depth at the center of HCP and LCP, respectively. ERT measurements were performed along the transect daily using the Wenner-Schlumberger configuration with an electrode spacing of 0.5 m. Other measurements and conditions useful for our synthetic studies -including soil temperature, soil moisture, thaw depth, snow dynamics and climate conditionswere also measured (Dafflon et al, 2017). These data have been used here to develop conceptual models and synthetic columns, while they will be used for real application of the joint inversion scheme in a subsequent study.…”
Section: Synthetic Soil Column Description and Boundary Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microtopography is the topographic variation on the order of submeters to several meters, which can be characterized mainly through airborne light detection and ranging (LiDAR) data. Recent studies conducted in Arctic regions—using high‐resolution geophysical and remote sensing data—have revealed that microtopography could produce significant spatial heterogeneity in soil moisture and plant community distributions at several‐meter or submeter scales (S. S. Hubbard et al, ; Dafflon et al, ; H. M. Wainwright et al, ). While the slope aspect of the hillslopes can be considered as a first‐order large‐scale control (Pelletier et al, ; Yetemen et al, ), the controlling factors within each hillslope have not yet to the authors' knowledge been investigated.…”
Section: Introductionmentioning
confidence: 99%